PERAN GURU DALAM MENANAMKAN NILAI-NILAI KARAKTER SISWA DALAM PEMBELAJARAN KURIKULUM 2013 PADA SISWA KELAS 1 MIN 1 BANTUL YOGYAKARTA TAHUN AJARAN 2016/2017 - Sukati, Sukati; Fathiyyah, Rizkiyatul (AL-MISBAH (Jurnal Islamic Studies), 2017)
The background of this research is education is the main need and responsibility for parents, government and society. Given the role of classroom teachers in teaching the curriculum lessons of 2013, not only teaching but also has the obligation in instilling the values of student characters so that the form of a positive character in accordance with the expected goals. This study aims to determine the role of teachers in inculcating the values   of the character of students, to know the character values   implanted by teachers and to determine the inhibiting factors and supporters in instilling the values   of student characters in class 1 MIN 1 Bantul Yogyakarta academic year 2016 / 2017.The type of research used in this study is the type of field research (field research), with a qualitative descriptive approach. While the techniques and instruments of data collection with observation, interviews, and documentation. As well as techniques Data analysis used in this study is descriptive analysis method.The results of this study indicate that: 1) the role of teachers in inculcating the values   of student character in learning curriculum 2013 in grade 1 students in MIN 1 Bantul Yogyakarta, among others: role as role model, inspirator, motivator, dynamator, facilitator and evaluator. Through discussion method, question and answer method, demonstration method and plus lecture method. 2) The values   of character education implanted in MIN 1 Bantul Yogyakarta consist of 3 categories namely a) values   that are often inculcated include religious values, honest, tolerance, hard work, creative, independent, curiosity, love peace, caring Environment and social care. B) character values   rarely instilled in thematic learning are discipline, hard work, democracy, nationalism, respect for achievement, friendly / communicative, and responsibility. C) values that are not implanted at all based on indicators in the observation guidelines by the researcher that is the value of love the homeland and the value of reading. 3) factors supporting the role of teachers in instilling students? character values   include: parents, school routine programs, facilities, and school committees. While the inhibiting factors are the lack of attention of parents, environment, learners and the state of the class.